Report on an Analysis of Spindle Whorl from Callao Cave, Peñablanca, Northern Luzon Philippines - Cameron, Judith; Mijares, Armand Salvador (Hukay; Vol 9 (2006), 2016)
During the 1980 archaeological excavation at Callao Cave in Northern Luzon, a clay spindle whorl was recovered. This spindle whorl was recently analysed and compared with whorls from other known sites. The Callao spindle whorl has similar attributes, like material composition, shape and weight, with  those excavated at the Fengpitou site in Taiwan. These similarities betwem spindle whorls of Taiwan and the northern Philippines could  be taken as evidence to support the Out-of-Taiwan model in explaining the spread of the Austronesian-speaking people.